(15) Study on the Development of the Egyptian National Fleet دراسة حول تطوير الأسطول الوطني المصري - Farahat, Ahmad; Ali, Tharwat Mohamed; Abdel Rahman, Yehia (معهد التخطيط القومى, 2021)
Foreign trade is one of the main contributors to economic growth. This activity fundamentally relies on the provision of transport means at reasonable prices, making shipping an important factor in the development process. However, statistics on international shipping and trade movements reveal a low and inadequate participation of developing countries in the maritime transport of trade generated by these countries, particularly in the bulk sector. This situation prompted the United Nations Conference on Trade and Development (UNCTAD) at its recent meeting in Manila in May 1979 to urge developing countries to expand their national merchant marines. This issue is viewed as a principal step in implementing the Program of Action on the Establishment of a New International Economic Order, which states that "all efforts should be made to promote an increasing and equitable participation of developing countries in the world shipping tonnage." Locally, the situation in Egypt is even worse, with the share of national vessels in freight and tonnage being considerably low (less than 10%). Additionally, a significant portion of the current fleet's tonnage capacity has exceeded its economic lifespan, and the fleet composition reveals a severe deficiency in the availability of specific ship types, particularly bulk and grain carriers.